Psychosocial Well-Being of Israeli Students and Attitudes toward Open and Distance Learning - Kurtz, Gila; Amichai-Hamburger, Yair; Kantor, Jeffrey (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This article reports on a study conducted in Israel at an academic institution. The study investigates the correlation between students’ attitudes toward open and distance learning (ODL) and their perceived self-esteem and loneliness at the last stage of their online learning experience. For this study, 120 students were asked to complete a questionnaire. The students were enrolled in three fully online academic courses, which were similar in their instructional design approach although different in content. Findings reveal that there is a positive correlation between self-esteem and attitudes toward e-learning in general and toward online interaction with the instructor in particular. The findings further suggest that there is no correlation between loneliness and student attitudes toward e-learning. Some explanations for these results are raised as are recommendations for further research.